Visualization of Probiotic-Mediated Ca2+ Signaling in Intestinal Epithelial Cells In Vivo - Adachi, Takahiro; Kakuta, Shigeru; Aihara, Yoshiko; Kamiya, Tomonori; Watanabe, Yohei; Osakabe, Naomi; Hazato, Naoki; Miyawaki, Atsushi; Yoshikawa, Soichiro; Usami, Takako; Karasuyama, Hajime; Kimoto-Nira, Hiromi; et al. (Frontiers in Immunology, 2016)
Probiotics, such as lactic acid bacteria (LAB) and Bacillus subtilis var. natto, have been shown to modulate immune responses. It is important to understand how probiotic bacteria impact intestinal epithelial cells (IECs), because IECs are the first line of defense at the mucosal surface barrier and their activities substantially affect the gut microenvironment and immunity. However, to date, their precise mechanism remains unknown due to a lack of analytical systems available for live animal models. Recently, we generated a conditional Ca2+ biosensor Yellow Cameleon (YC3.60) transgenic mouse line and established 5D (x, y, z, time, and Ca2+) intravital imaging systems of lymphoid tissues including those in Peyer’s patches and bone marrow. In the present study, we further advance our intravital imaging system for intestinal tracts to visualize IEC responses against orally administrated food compounds in real time. Using this system, heat-killed Bacillus subtilis natto, a probiotic TTCC012 strain, is shown to directly induce Ca2+ signaling in IECs in mice housed under specific pathogen-free conditions. In contrast, this activation is not observed in the Lactococcus lactis strain C60; however, when we generate germ-free YC3.60 mice and observe the LAB stimulation of IECs in the absence of gut microbiota, C60 is capable of inducing Ca2+ signaling. This is the first study to successfully visualize the direct effect of probiotics on IECs in live animals. These data strongly suggest that probiotic strains stimulate IECs under physiological conditions, and that their activity is affected by the microenvironment of the small intestine, such as commensal bacteria.